Taxes in America : what everyone needs to know - Burman, Leonard; Slemrod, Joel. (Oxford ; New York : Oxford University Press, 2013)
Most contemporary Americans know little about how their tax system works. But with heated debates over taxation now roiling Congress and the nation, an understanding of our tax system is of vital importance. In this book the authors, both tax scholars, offer explanations of how our tax system works, how it affects people and businesses, and how it might be improved. Organized in a question-and-answer format, the book describes the intricacies of the modern tax system. The authors begin with the basic definitions of taxes and then delve into more complicated and indeed contentious concerns. They address such questions as how to recognize Fool's Gold tax reform plans ; How much more tax could the IRS collect with better enforcement? ; How do tax burdens vary around the world? ; Why do corporations pay so little tax, even though they earn trillions of dollars every year? ; And what kind of tax system is most conducive to economic growth? They discuss key issues such as the large number of social programs hidden in the tax code, how taxes affect the economy, how the burdens of taxation are distributed, and the costs of running the tax code on both the IRS and taxpayers. They also dive into the political process, the genesis of ill-advised tax ideas, and options to improve the tax system. With the U.S. struggling to recover from the deepest economic recession since the 1930s, facing a mountain of debt, it is important for Americans to understand the tax system. This book describes modern tax realities, and educates Americans about the issues in the debate about tax reform.
pt. III. A tour of the sausage factory : 10. Misperceptions and reality in the policy process: What does the public know about taxes?, What does the public think about taxes?, How are new taxes enacted?, What are regulations and why are they important?, How does the tax sausage get made? (House and Senate rules), Who estimates the revenue impact of tax changes?, How do they do it? Do they ignore behavioral responses to taxation?, What is dynamic scoring?, Must taxes be raised?, Can we solve the problem by raising tax rates only on those with high incomes? ; 11. Snake oil: The FairTax sounds, well, fair : is it?, Wouldn't a flat tax be super-simple and efficient?, How about offering a new tax system on an elective basis?, What is the "starve-the-beast" theory?, Does the taxpayer protection pledge protect taxpayers?, What is the "two Santa Claus" theory? ; 12. Tax reform: Tax reformers talk about a broad base and low rates. What does that mean?, Is the broadest base always the best base?, Does the framing of taxes matter?, What is a revenue-neutral tax change?, Should tax reform and deficit reduction be separated?, Are there some sensible tax reform ideas?, What have we learned?
Includes bibliographical references and index.
Keywords: Taxation -- United States; Taxation; United States; Steuer; USA; Taxation -- United States